Project-based management to reduce skin damage associated with acupressure medical adhesives in patients undergoing acupoint application for chronic gastritis (基于项目化管理降低慢性胃炎患者穴位贴敷医用粘胶相关性皮肤损伤) - WANG Qian (王倩); WANG Jiehong (王捷虹); SHA Zhihui (沙志惠) (中西医结合护理)
Objective To evaluate the project-based management in reducing acupressure medical adhesive-associated skin injury in patients with chronic gastritis, and provide a reliable basis for clinical practice. Methods Take the tendency score matching method, 1: 1 matching to find control. Finally, 235 cases of chronic gastritis were selected from the Department of Gastroenterology from October 2021 to March 2022 as the intervention group (2215 times of application) for project management; From October 2020 to March 2021, 235 patients with chronic gastritis were used as the control group (2215 times of application) and were managed by traditional mode, comparing the quality management results of the specific work, associated skin damage, and pain scores at removal of the acupressure applied in both groups. Results By adopting the project-based management model, the overall target achievement rate reached 93. 27% and the overall progress rate reached 63. 95%, which was better than the target and achieved the expected results, in which the quality monitoring results of the intervention group were significantly higher than those of the control group (P<0. 05), and the incidence of skin redness and total skin injury and pain score when removing the acupressure in the intervention group were significantly lower than those of the control group (P<0. 05). Conclusion The quality of project-based management can improve the quality management of acupressure-specific situations, can change the skin damage associated with acupoint application, and alleviate pain when removing acupressure, thereby reducing patient discomfort and improving the quality of Traditional Chinese Medicine care. (目的 基于项目化管理降低慢性胃炎患者穴位贴敷医用粘胶相关性皮肤损伤(MARSI), 为临床操作提供可靠依据。方法 采取倾向性得分匹配方式, 1: 1匹配找对照。最后选取消化内科2021年10月—2022年3月实施穴位贴敷的235例慢性胃炎患者作为干预组(贴敷2215次), 进行项目化管理; 2020年10月—2021年3月进行穴位贴敷的235例慢性胃炎患者作为对照组(贴敷2215次), 采用传统模式进行管理。对比两组患者穴位贴敷的专项工作质量管理结果、相关性皮肤损伤情况、揭除时疼痛评分。结果 通过采用项目化管理模式, 总体目标达成率达到 93. 27%, 整体进步率达到63. 95%, 较好地完成了目标, 并取得预期成效。干预组的质量监控结果评分高于对照组(P＜0. 05), 干预组患者的皮肤发红和总的皮肤损伤发生率、撕除穴位贴敷时疼痛评分均低于对照组(P＜0. 05)。结论 项目化管理的质量可以提升穴位贴敷专项质量管理情况, 改善与穴位贴敷的相关性皮肤损伤情况, 缓解撕除穴位贴敷时的痛苦, 减轻患者的不适感, 同时提升中医护理质量。)